FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENCARIAN PELAYANAN KESEHATAN (HEALTH SEEKING BEHAVIOUR) PADA MAHASISWI PRODI KEPERAWATAN YANG MENGALAMI KELUHAN DISMENORE DI UNIVERSITAS DIPONEGORO - Fajar Luthfir Rahman; Priyadi Nugraha P.; Emmy Riyanti; Syamsul Huda BM (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dysmenorrhea is a disorder during the outbreak of menstrual blood flow or pain that occurs when the arrival of menstrual cycle or menstruation is usually followed by a sense of cramp and centered on the lower abdomen. In a study of 50 students in Semarang conducted by Ernawati in 2010 found mild dysmenorrhea incidence as much as 18%, moderate dysmenorrhea 62% and dysmenorrhea weight 20%.The purpose of this study was to analyze factors related to health seeking behavior in nursing students who had dysmenorrhea complaints at Diponegoro University. This research method is quantitative with cross sectional study. The population are Diponegoro University nursing students of 2014 and 2015 who have dysmenorrhea complaints with a total of 79 people and the sample uses a total population of 79 people, with total sampling method. Most of the respondent's age is 17-20 years old (late teens). Respondents had an older sister who had dysmenorrhea (22.8%), respondents have less health information quality as much as (63,3%), knowledge of respondents in high category (84.8%), permissive attitude (70.9%), poor perception (55.7%), availability of health services and support costs (72.2%), access to health services support (43%) and perception of individual needs about dysmenorrhea (65.8%). The result of the research is correlation between the information source (p = 0,034) and attitude (p = 0,028) with the searching of health service.